Investigation of potential cognition factors correlated to fire evacuation - Yan, Jingjing; He, Gengen; Basiri, Anahid (Springer, 2020)
The design of a navigation system to support indoor fire evacuation depends not only on speed but also a relatively thorough consideration of the cognition factors. This study has investigated potential cognition factors which can affect the human behaviours and decision making during fire evacuation by taking a survey among indoor occupants in age of 20s under designed virtual scenarios. It mainly focuses on two aspects of Fire Responses Performances (FRP), i.e. indoor familiarity (spatial cognition) and psychological stress (situ-ated cognition). The collected results have shown that these cognition factors can be affected by gender and user height and they are correlated with each other in certain ways. It has also investigated users‟ attitudes to the navigation services under risky and non-risky conditions. The collected answers are also found to be correlated with the selected FRP factors. These findings may help to further design of personalized indoor navigation support for fire evacuation.